THE EFFECT OF ELECTRONIC WORD OF MOUTH AND TIKTOK INFLUENCER CREDIBILITY ON PURCHASE DECISIONS OF LOCAL CLOTHING PRODUCT AMONG GENERATION Z UNIVERSITY STUDENTS IN MAKASSAR CITY - Warani, Yardan Arif; Natsir, Uhud Darmawan; Abadi, Rahmat Riwayat; Mustafa, Muh. Yushar (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the effect of Electronic Word of Mouth (eWOM) and Influencer Credibility on Purchase Decisions of Local Clothing products among Generation Z students. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 104 Generation Z students who actively use TikTok as a social media platform. The data analysis techniques included validity and reliability tests, classical assumption tests, and multiple linear regression analysis using SPSS software.Keywords: Electronic Word of Mouth, Influencer Credibility, Purchase Decision, Local Clothing, Generation Z.